Factors Influencing SME Financing: Case in Indonesian Islamic Bank - Mahmada Azmi Maulida; Nur Hidayah; Imron Rosyadi (IECON: International Economics and Business Conference, 2023)
Islamic Commercial Banks is one of the institutions that provide financing for Small and Medium Enterprises (SMEs). This study aims to analyze the effect of Third Party Funds (DPK), Inflation, Non-Performing Financing (NPF), and Margin Levels on Small and Medium Enterprises (PUKM) financing in Islamic Commercial Banks. The type of data used in this study is secondary data derived from monthly statistical reports on Islamic banking which are accessed through the official website of the financial services authority and the website of Bank Indonesia. The period of this research is from 2016 to 2021. The analytical method used is Ordinary Least Square (OLS). The results of the study concluded that DPK and Margin Level had a significant effect on PUKM. While inflation and NPF have no significant effect on PUKM. Islamic commercial banks as intermediary institutions can increase financing for SMEs by maximizing DPK and margin levels in the hope that financing for SMEs can increase economic growth in Indonesia.